Designing and testing of a smart firefighting device system (LAHEEB) - Samkari, Yousef; Guedri, Kamel; Oreijah, Mowffaq; Munshi, Shadi; Azam, Sufyan (IAES International Journal of Robotics and Automation (IJRA), 2020)
The motivation behind this project is that firefighter's death. Many firefighters are struggling to perform their duty which causes much death while on a mission and the circumstances related to each incident. Firefighters are our heroes and our sense of security in times of trouble. They put themselves on dangerous situations to protect us. At present, the world is moving toward the use of technologies software and hardware. This paper proposed a smart firefighting device system (LAHEEB) which designed to detect the source of fire, extinguish it, and increase the knowledge about fire behavior from incident area. This device can extinguish different types of fire A, B, C, D, F/K, electric and metal fire without spreading in the shortest time. This device will reduce the risk of injury for firefighters and possible victims and decrease the monetary losses which increase considerably as fire duration increases. LAHEEB device is consists of two parts. The first part is called the mid-cap which presented the body of the device that has most of the components such as sensors, relays, battery, servo motor, liquid tank, push-button, and Arduino. The second part is called the bottom-cap which presented the moving part of the device that has the significant components of LAHEEB such as servo motor, sprayer, and thermal camera. It also makes use of liquid-tank and spray mechanism for extinguishing the fire. The spraying nozzle is mounted on a servo motor to cover maximum area. Liquid-extinguisher is pumped from the main tank to the nose with the help of a pump. The whole system is programmed using an Arduino DUE board which forms the brain of the system.